2020
DOI: 10.17269/s41997-020-00382-7
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and circadian rhythm in response to the COVID-19 pandemic

Abstract: This commentary highlights the critical role of sleep as a public health issue, particularly during a stressful life period such as the COVID-19 pandemic, and provides evidence-based practical guidelines to manage sleep disturbances during this crisis. The COVID-19 pandemic and the imposed social confinement have produced significant stress, anxiety, and worries about health and the fear of being infected, jobs and financial problems, and uncertainty about the future. The incidence of sleep disturbances has al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
186
1
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(215 citation statements)
references
References 14 publications
9
186
1
19
Order By: Relevance
“…Forced lockdown such as during the current pandemic disrupts timing and duration of exposure to ambient light, the most important environmental Zeitgeber [16]. The use of mobile phones, tablets, and computers to watch the news, binge-watching of web series, and connecting on social media leads to excessive screen time in evening hours [17]. The blue light emitted from screens suppresses the natural production of melatonin at night.…”
Section: The Aged Circadian Clock Networkmentioning
confidence: 99%
“…Forced lockdown such as during the current pandemic disrupts timing and duration of exposure to ambient light, the most important environmental Zeitgeber [16]. The use of mobile phones, tablets, and computers to watch the news, binge-watching of web series, and connecting on social media leads to excessive screen time in evening hours [17]. The blue light emitted from screens suppresses the natural production of melatonin at night.…”
Section: The Aged Circadian Clock Networkmentioning
confidence: 99%
“…The uncertain situation and the governmental measures resulted in changes in sleep and sleep timing around the globe. Some research groups showed increasing prevalence of sleep problems (insomnia, sleep loss, poor sleep quality) in healthcare workers and the general population [5][6][7][8][9], while others showed an improvement of sleep health. In India, China, and Italy, people slept later and longer [2,7,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to pay attention to sleep during the COVID-19 pandemic because sleep plays a major part in sustainable health. Good night sleep (consisting of sleep duration/quality and timing) is essential to build resilience and cope with the primary and secondary effects of disease [ 8 ]. We hypothesized that sleep timing and therefore overall sleep in evening-oriented people during the changed circumstances is more in line with their biological needs and thus beneficial to health.…”
Section: Introductionmentioning
confidence: 99%
“…This effect may be due to the psychological impact of the COVID-19 since 18.7% and 21.6% of the Spanish population have been potentially diagnosed of depression and anxiety respectively [45]. In addition, the isolation situation causes less time spent outdoors and exposure to sunlight is a determining factor in the regulation of internal circadian rhythms, fundamental to the sleep pattern [46]. Likewise, sleep disruption was associated with a higher BMI.…”
Section: Discussionmentioning
confidence: 99%